The role of J. A. Atkinson in the development of panoramas in Russian art - Skvortsova, Ekaterina A. (Actual Problems of Theory and History of Art, 2025)
The article offers careful scrutiny of the meaning of a term ‘panorama’ and its transformation and an overview of the evolution of the phenomenon in both European and Russian art with an emphasis on the difference between genuine panoramas and what we usually call so now. The author reaches the conclusion, that J. A. Atkinson was one of the pioneers of this genre in Russia and the first artist to display a panorama of Russian city in Europe.
Keywords: panorama; circular panorama; stationary and moving panoramas; miniature and monumental panoramas; Russian -English artistic links; artists-travellers